Prevalence of metabolic syndrome among workers from the Company of Generation and Distribution of Energy in Rio de Janeiro, Brazil - Luiz Stanislau Nunes Chini; Suzana Greffin; Jocemir Ronaldo Lugon (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2014)
Little is known about the prevalence of metabolic syndrome in the World's working force. We examined the prevalence of such disease in the Company of Generation and Distribution of Energy in Rio de Janeiro city, Brazil.METHODS: A cross-sectional study was designed to analyze data from employees submitted to the annual company medical check-up in 2008. Medical charts were reviewed for collection of clinical and laboratorial information.RESULTS: The total prevalence of metabolic syndrome was 48.6% (95%CI 46.0-51.2). It increased with age and reached 58.7% (95%CI 56.1-61.3) in employees older than 60 years. The age- adjusted prevalence was 38.2% (95%CI 35.7-40.7). Increased waist circumference was the most prevalent component of the syndrome (94.2%; 95%CI 92.1-95.7), followed by high blood pressure (69.3%; 95%CI 65.7-72.7). In a multivariate analysis age, sedentary lifestyle and level of uric acid were significantly associated with the metabolic syndrome.CONCLUSION: Metabolic syndrome is highly prevalent in the studied working population in Rio de Janeiro. Our study will help delineating key risk factors for the development of metabolic syndrome in Brazil and may help the creation of new preventive public health policies.